The Function of Inland Shipping on Economic Supporting Activities of the South Kalimantan Community 1980-2000 - Muhammad Rico (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The main problem examined in this research is how the function of inland shipping is to support the economic activities of the people of South Kalimantan in 1950-1970 The results of the research show that the river network has become the economic lifeblood of the population where most of their economic activities are carried out through and on rivers due to shipping activities. Rivers cannot be separated from their role as trade routes. River shipping has an important role in transporting trade goods. Agricultural products and forest products are one of the main commodities transported via river shipping. As a means of traffic, rivers play a role in opening up the isolation of inland areas that cannot be passed by land. The method used in this research uses the historical method through the Heuristic stage (data collection), internal and external criticism of the data obtained, interpretation and historiography of historical writing based on the data that has been obtained according to the researcher's objectives. The novelty of this research is that previous research only revealed the phenomenon of river shipping broadly, then this research focuses on the economic sector. It can be concluded that with the times and the rapid development of technology, the transportation sector has developed. The widespread development of land transportation facilities by creating land roads and bridges to connect between regions can shorten distances and travel times. However, it even has an impact on the economic sector through water transportation routes.